A Multidimensional Development Theory Perspective on Mobile Fintech Privacy: Evidence from Indonesian Millennial Users - Purwantini, Anissa Hakim; Maharani, Betari (Jurnal Analisis Bisnis Ekonomi, 2024)
In today's digital economy, privacy concerns in the context of financial technology (FinTech) have become critically important. This research aims to investigate both the enabling and inhibiting factors influencing Internet Privacy Concern (IPC) among users of mobile FinTech services, specifically targeting the millennial generation in Indonesia. The research model is grounded in the Multidimensional Development Theory, encompassing four dimensions: environmental, individual, information management, and interaction management. This study employed an online survey method to distribute questionnaires to respondents, and through convenience sampling, 432 respondents were obtained. Utilizing Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis, the results demonstrate that familiarity with government legislation, risk avoidance and privacy protection have positif effect on IPC. While industry self- regulation, collectivism, previous privacy invasion experience, internet knowledge, information sensitivity and social presence did not influence IPC. Furthermore, benefit of information disclosure has a negative effect on IPC.